2018
DOI: 10.1369/0022155418812405
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Junctions and Invaded Macrophages in Oral Epithelia With Oral Pain

Abstract: Recurrent or chronic oral pain is a great burden for patients. Recently, the links between epithelial barrier loss and disease were extended to include initiation and propagation. To explore the effects of pathohistological changes in oral epithelia on pain, we utilized labial mucosa samples in diagnostic labial gland biopsies from patients with suspected Sjögren's syndrome (SS), because they frequently experience pain and discomfort. In most labial mucosa samples from patients diagnosed with SS, disseminated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 89 publications
0
4
0
Order By: Relevance
“…One study found that high expression of gamma delta T cells in the peripheral blood of patients with pSS may play an auxiliary role in inducing B cells to secrete immunoglobulins and may participate in the pathological immune response of pSS (Gerli et al, 1993). Yoshimoto et al (2019) also found that most lip epithelial sections of SS patients showed cellular edema infiltrated by macrophages, which may be one of the characteristics of SS. pSS patients have elevated plasma cell levels in the peripheral blood, and the number of IgG4 + plasma cells that infiltrate the salivary glands is negatively correlated with disease characteristics; the higher the IgG4 + expression in plasma cells, the lower the positive rates of serum anti-SSA antibodies, anti-SSB antibodies, antinuclear antibodies and rheumatoid factor (Liu et al, 2017;Brokstad et al, 2018).…”
Section: Discussionmentioning
confidence: 78%
“…One study found that high expression of gamma delta T cells in the peripheral blood of patients with pSS may play an auxiliary role in inducing B cells to secrete immunoglobulins and may participate in the pathological immune response of pSS (Gerli et al, 1993). Yoshimoto et al (2019) also found that most lip epithelial sections of SS patients showed cellular edema infiltrated by macrophages, which may be one of the characteristics of SS. pSS patients have elevated plasma cell levels in the peripheral blood, and the number of IgG4 + plasma cells that infiltrate the salivary glands is negatively correlated with disease characteristics; the higher the IgG4 + expression in plasma cells, the lower the positive rates of serum anti-SSA antibodies, anti-SSB antibodies, antinuclear antibodies and rheumatoid factor (Liu et al, 2017;Brokstad et al, 2018).…”
Section: Discussionmentioning
confidence: 78%
“…As TRPV4 agonists or antagonists can regulate inflammation in pulmonary or bowel disease models, TRPV4 has been implicated as a potential target for the management of lung injury or inflammatory bowel diseases . In addition, we recently revealed an impairment of the epithelial cell‐cell contact structure with an irregular pattern of adherens junctional proteins and TRPV4 in the labial mucosal epithelium of Sjögren syndrome patients . Impaired epithelia with weaker TRPV4 expression than normal epithelia were observed together with a larger number of inflammatory cells in Sjögren syndrome patients.…”
Section: Discussionmentioning
confidence: 94%
“…36 In addition, we recently revealed an impairment of the epithelial cell-cell contact structure with an irregular pattern of adherens junctional proteins and TRPV4 in the labial mucosal epithelium of Sjögren syndrome patients. 37 Impaired epithelia with weaker TRPV4 expression than normal epithelia were observed together with a larger number of inflammatory cells in Sjögren syndrome patients. Thus, TRPV4-associated epithelial cell-cell junctions appear to play an important role in human oral mucosal epithelia.…”
Section: As Light Microscopic Observation Indicated Wider Intercellu-mentioning
confidence: 95%
“…In this regard, the study by Antunes et al [ 206 ] found that oral supplementation with capsaicin reduced macrophage infiltration and IL-33 production in proximal jejunum in a mouse model of OVA allergy. The study by Yoshimoto et al [ 207 ] explored the effects of the pathohistological changes in oral epithelia on pain by using labial mucosa samples from patients with suspected Sjogren’s syndrome (SS) because they frequently experience pain and discomfort. The disrupted epithelia contained high numbers of infiltrating macrophages and remodeled cell adhesion molecules such as filamentous actin, E-cadherin, or β-catenin.…”
Section: Potential Of Oral Mucosa Characterization In Diagnosis and Treatmentmentioning
confidence: 99%